白殭蠶이 남성 골다공증에 미치는 영향 - 김호현(Ho Hyun Kim); 안상현(Sang Hyun Ahn); 박선영(Sun Young Park) (동의생리병리학회지, 2019)
To investigate the effect of Bombycis Corpus on male osteoporosis, we performed Dual Energy X-Ray Absorptiometry(DEXA) and histochemical methods. The animals were used ICR-based male mice of 8 weeks and 50 weeks, respectively. ICR male mice at 8 weeks were used in the control group, and ICR male mice at 50 weeks were used in aging group and Bombycis Corpus group(BC group). In the aging group, 0.5 ml of distilled water was administered once a day for 6 months. In BC group, Bombycis Corpus(0.78g/kg) was dissolved in distilled water for 6 months once a day. As a result, Bombycis Corpus decreased bone loss, increased bone density by reducing the loss of bone matrix in the femur due to aging, and increased osteoblast – induced osteopontin(OPN) and osteocalcin(OPC) positivite reaction. In addition, administration of Bombycis Corpus decreased Reaction of activation of nuclear factor kappa B ligand(RANKL) positive reaction, increased osteoprotegerin(OPG) positive reaction, and decreased matrix metalloproteinase-3(MMP-3) and 8-hydroxy-2' -deoxyguanosine(8-OHdG) positivite reaction. Taken together, Bombycis Corpus increases the activity of osteoblasts, inhibits osteoclast function, promotes osteoblast function, inhibits bone tissue degradation, and inhibits bone loss due to oxidative stress. It was observed that Bombycis Corpus reduced bone loss and increased bone density caused by aging to improve male osteoporosis. Therefore, Bombycis Corpus may be used as a preventive and therapeutic agent for male osteoporosis. KCI Citation Count: 0